Niveles de comprensión lectora según género en estudiantes del 5° de primaria de instituciones educativas del Callao - Huamán Díaz, Maritza Antonia (2012)
Sought to describe and compare the levels of reading comprehension, according to gender. The sample comprised 100 students, 50 girls and 50 boys in the 5th grade educational institutions of Callao. The ACL5 º (Catala et al 2001) testwas applied adapted (Gomez, 2009). The results showed that 10% of boys and 16% of girls are at a very low level, 22% of boys and 30% of girls are at a low level, 44% of boys and 30% of girls are moderately low, 22% of boys and 18% of girls are within normal limits, the high level was reached by only 2% of boys and 6% of girls. The data show low performance in reading comprehension. In addition, we determined that there are no significant differences in levels of reading comprehension by gender.